A panorama of the sacred at Teresina: the territorialization of religion in the city, Piaui State, Brazil (Research, Society and Development, 2020)
Religions assume a prominent role in the face of the cultural formation of society, influencing the way man relates to space. Thus, studying the urban space considering the perspective of the Sacred enables a particularized understanding of the city. This work has as study part, the city of Teresina, in contemporary times, and tries to understand how religions are territorialized in this capital. Thus, the objective is to present a panorama of the territorialization of the sacred in the urban space of Teresina. Were selected for the research: afrobrazilian religions such as Umbanda and Candomblé; the Catholic Church; the neo-pentecostal evangelical churches Assembly of God and Universal Church of the Kingdom of God; and the Baptist Church, traditional Protestant. From a qualitative approach, we sought to map the religious densities, describing the territorialities in order to expand the knowledge of this human / urban index, sometimes neglected, or underreported, contributing to the urban planning and management policy. It was concluded that the expression of religion in space transcends the constructed matter, and it is through the experience of the users, that is, through their sociability relations that the greatest influence of the Sacred is given off.